Rheological behavior of Sheet Molding Compounds (SMC) with short glass fiber - Tung, Nguyen Huy; Chuong, Bui; Hung, Le Thai; Dat, Nguyen Quy (Vietnam Journal of Chemistry, 2015)
The thermal-mechanical behaviour of SMC was investigated. The experimental results emphasized the influence of the imposed strain rate, the mass fraction of fibers, BYK lubricant, as well as the temperature on the SMC rheological behaviour. The stress of SMC was increased while increasing  volume fraction and fiber length. However, the raising of temperature  reduced the stress of SMC. From the relationship rate between stress and strain we may identify the consistency of materials and the strain rate sensitivity, thereby strain hardening of SMC materials is known. Keywords. SMC, rheology, glass fiber.